Amido-3-hydroxypyridin-4-ones as iron(III) ligands - Piyamongkol S. (2014)
The synthesis and physicochemical properties of a range of 2and 6-amido-3-hydroxypyridin-4-ones are described. All the amido-substituted 3-hydroxypyridin-4-ones have lower pK a values than 1,2-dimethyl-3-hydr-oxypyridin-4-one (deferiprone). This is due to the inductive effect of the amido group. Furthermore, the pK a values of the 3-hydroxy group in 1-nonsubstituted pyridinones are dramatical- Iy lower than those of the corresponding 1-alkyl analogues, indicating that a strong hydrogen bond exists between the 2-amido function and the 3-oxygen anion, which stabilises the anion. As a result of the decreased competition with protons, the pFe 3+ values of this group of molecules are higher than that of deferiprone. The distribution coefficients of these molecules are also increased despite the lack of a hydrophobic 1-alkyl substituent and this is ascribed to the intramolecular hydrogen bond. X-ray diffraction studies confirm the existence of the intramolecular hydrogen bond. © 2010 Wiley-VCH Verlag GmbH & Cu. KGaA. Weinheim.